Isolation and analysis of citral from Cymbopogon citratus (DC) (Fam. Gramineae) - Ortega, Adolfo M.
Extraction of the essential oil from Cymbopogon citratus (DC) Stapf by steam distillation using a Clevenger apparatus for oils lighter than water. A total of 2037 g. of the plant material was used in successive extraction of the oil. The oil yield was 4.95 mL (0.23%) based on the crude extract and after drying over anhydrous sodium sulfate, it became roughly 3.5 mL. The oil was stored in a tight, amber colored bottle in the refrigerator.